Tuning the on/off current ratio in ionic-liquid gated multi-layer MoS2 field-effect transistors - Jeon, Dae-Young; Nam, Deuk Hyeon; Lee, Dong Su; Lee, Seoung-Ki; Park, Min; Park, So Jeong; Kim, Gyu-Tae (IOP PUBLISHING LTD, 2020)
Ionic-liquid gated multi-layer MoS2 field-effect transistors were fabricated and their electrical properties related to maximum depletion depth, bulk neutral and surface accumulation conduction were investigated in detail. A negative back-gate bias resulted in a depletion of the bulk neutral channel at the bottom interface, which significantly enhanced transistor performance in terms of the on-current to off-current (I-on/I-off) ratio and the off-state current level. The experimental results were verified by numerical simulations and analytical equations. These findings are critical for the optimization of the I-on/I-off ratio of multi-layer MoS2 transistors for energy efficient electronics and low power applications.
Keywords: HIGH-PERFORMANCE